2022
DOI: 10.3390/su142316121
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Environmental, Social, and Governance Management Research from 2002 to 2021

Abstract: Extreme weather events caused by climate change have increased people’s focus on sustainability. Environmental, social, and governance management (ESGM) has become crucial for corporate operations and development; ESGM has attracted the attention of the academic communities, and the number of related studies has continued to increase. However, this topic is multidisciplinary and diverse; therefore, this study used the Web of Science Core Collection Database to conduct a bibliometric analysis of ESGM-related ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…It is a widely used, effective and reliable approach to measure, analyse and visualise bibliometric data of a larger set of publications by using quantitative and visualising analysis approaches (Daim et al, 2006;Rusly et al, 2019). Bibliometric analyses are very useful for assessing existing literature to obtain valuable insights on the knowledge development of a particular area of research for different interested parties such as academicians, practitioners, business organisations and policymakers (Qian & Sun, 2022;Siao et al, 2022;Zainuldin & Lui, 2022). Therefore, this bibliometric analysis is conducted to explore the knowledge structure of combined TA-CSR research publications for identifying current state of knowledge and future directions to advance the existing knowledge (Baker et al, 2020a;Priyashantha et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a widely used, effective and reliable approach to measure, analyse and visualise bibliometric data of a larger set of publications by using quantitative and visualising analysis approaches (Daim et al, 2006;Rusly et al, 2019). Bibliometric analyses are very useful for assessing existing literature to obtain valuable insights on the knowledge development of a particular area of research for different interested parties such as academicians, practitioners, business organisations and policymakers (Qian & Sun, 2022;Siao et al, 2022;Zainuldin & Lui, 2022). Therefore, this bibliometric analysis is conducted to explore the knowledge structure of combined TA-CSR research publications for identifying current state of knowledge and future directions to advance the existing knowledge (Baker et al, 2020a;Priyashantha et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The Scopus database was selected for collecting articles as it is a widely used comprehensive database to perform bibliometric reviews in many disciplines (Priyashantha et al, 2022). The search terms to collect data from the database were identified referring to existing literature to gathering more relevant and appropriate publications for the analysis (Ellili, 2022;Khan, 2022;Mumu et al, 2021;Siao et al, 2022). The identified search terms for the review were 'Tax avoidance' and 'CSR'.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Goel et al (2022) identified four themes based on a literature review performed on transmittable illnesses and tourism. Siao et al (2022) reviewed the trends in the last twenty years using the Web of Science database on environmental, social, and governance management (ESGM) using Bibliometrix, VOSviewer, and CiteSpace and analyzed how it was used to protect the environment and build value for organizations. Ruiz-Real et al (2018), in their research, analyzed the dynamics of circular economy for an eleven-year period by performing bibliometric analysis highlighting various trends and indicating that this domain has a very high potential for future research.…”
Section: Overview Of Bibliometric Studiesmentioning
confidence: 99%
“…It is also a research method for assessing the productivity of authors, countries, and institutions by revealing their global distribution, collaboration, knowledge structures development trends [3,4], depth topics, citations, citation times, and keyword co-occurrence based on Web of Science (WoS) database. While many bibliometric studies have been carried out in different scientific fields such as medicine, computing, geography, environmental science, social science, water management, and animal sciences for different purposes (e.g., [3][4][5][6][7][8][9][10]), limited studies have been carried out in forestry (e.g., [11,12]). In addition, published papers related to seed orchards have not yet been subjected to bibliometric analysis.…”
Section: Introductionmentioning
confidence: 99%